Cavity impact on the base flow unsteadiness for a high-speed exhaust system - Tsentis, Spyros; Goulos, Ioannis; Prince, Simon A.; Pachidis, Vassilios; Zmijanovic, Vladeta (American Society of Mechanical Engineers (ASME), 2024)
Future propulsion systems will be essential to enable sustainable high-speed flight and routine space access. Such concepts usually employ base-embedded, convergent-divergent nozzles and cavity regions to facilitate their mission, thus altering the flow dynamics at the base notably in comparison to contemporary launch vehicles. This paper presents a numerical investigation on the impact of a cavity region on the base flow unsteadiness for a sub-scale, high-speed exhaust system at over-expanded mode. The fully-installed model in the test section of a wind tunnel is employed to facilitate an ongoing experimental campaign. The Delayed Detached Eddy Simulation turbulence modeling approach is utilized to investigate the flow at the base. The configuration featuring the cavity is directly compared to a baseline apparatus, where the cavity has been removed, thus allowing for the impact of the cavity to be identified. Results show that the cavity region can reduce the base pressure fluctuations up to 20% and acts in a damping-like manner for the base flow unsteadiness. The total energy of the pressure fluctuations spectrum at the base can be reduced by as much as 38% compared to the baseline configuration. However, the impact of the cavity on the time-averaged pressure distribution at the base is negligible. Finally, the cavity is found to have a notable effect on the nozzle side loads, which are are reduced by an order of magnitude compared to the baseline case, and behave in an axisymmetric manner. This indicates that the cavity could act as a passive flow control mechanism for side loads reduction.
Keywords: 4012 Fluid Mechanics and Thermal Engineering; 40 Engineering; 4001 Aerospace Engineering; base cavity; hybrid RANS/LES; DDES; over-expansion; side loads; base drag; passive flow control